2015
DOI: 10.17129/botsci.256
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and genetic diversity of <em>Swietenia macrophylla</em> in areas subjected to selective logging in Quintana Roo, Mexico

Abstract: Abstract:The hypothesis that selective logging has a negative effect by altering the genetic parameters of tropical tree species was evaluated. The genetic diversity and genetic structure between adult trees (N = 47) and saplings (N = 50) of Swietenia macrophylla were contrasted within an area subjected to selective logging in the Mayan zone. Although differences in the number of alleles and in their frequencies were detected between both groups, the observed and expected heterozygosity and the coeffi cient of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Low-density populations generally show less structure and often an absence of SGS (Alcalá et al, 2014(Alcalá et al, , , 2015. The observed pattern of genetic structuring in S. macrophylla was mitigated by the long-distance pollination activities of generalist insects.…”
Section: Association Of Genetic Parameters With Forest Managementmentioning
confidence: 93%
See 1 more Smart Citation
“…Low-density populations generally show less structure and often an absence of SGS (Alcalá et al, 2014(Alcalá et al, , , 2015. The observed pattern of genetic structuring in S. macrophylla was mitigated by the long-distance pollination activities of generalist insects.…”
Section: Association Of Genetic Parameters With Forest Managementmentioning
confidence: 93%
“…Although the current forest management model incorporates the concept of reduced impact logging (RIL), it has been criticized for promoting the reproductive isolation of species and favoring non-random mating, which may contribute to increases in inbreeding and lead to genetic erosion. This is particularly this case for species such as S. macrophylla that generally present a low density (< 1 tree/ha) in natural populations (André et al, 2008;Sebbenn et al, 2008;Lacerda et al, 2013;Trujillo-Sierra et al, 2013;Alcalá et al, 2015). Genetic studies have reported that S. macrophylla has high levels of genetic diversity and differentiation among populations in areas without logging (Lemes et al, 2003;Degen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2009 ; Filazzola et al . 2020 ), influencing the strength of FSGS ( Alcalá et al . 2015 ; Chiriboga-Arroyo et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, canopy openness and changes in plant density can affect the microenvironmental conditions for seedling establishment and seed bank formation (Lobo et al 2007, Anthelme et al 2011, Álvarez-Aquino et al 2005, causing a decrease in late successional trees (Farwig et al 2008, Clark & Covey 2012. Moreover, a reduction of gene dispersal by pollen flow and seed dispersal and the decline in the number of reproductive individuals can decrease genetic diversity (Aguilar et al 2019) and increase the spatial clustering of genetically related individuals at the local scale in a pattern known as fine-scale genetic structure (FSGS) (Degen et al 2006, Ng et al 2009, Alcalá et al 2015. FSGS results from the combination of microevolutionary forces of genetic drift, selection, and adaptation that interact at the local scale (Kalisz et al 2001).…”
mentioning
confidence: 99%
“…Empirical evidence has shown that the intensity and spatial extent of FSGS may primarily depend on intrinsic factors, such as pollination and seed dispersal vectors, plant density, life form, mating system, and life stage (Vekemans & Hardy 2004, Dick et al 2008, Kloss et al 2011, Hoban et al 2014, Gelmi-Candusso et al 2017. However, extrinsic factors, such as habitat disturbance and selective logging may also play an important role (Ismail et al 2012, Hoban et al 2014, Alcalá et al 2015, Kitamura et al 2018. Empirical studies so far have shown contradicting findings.…”
mentioning
confidence: 99%